Medical Residents, the Group and the Formation of Professional Identity During the COVID-19 Pandemic - Oliveira, Francisco Arsego de; Corleta, Helena von Eye; Capp, Edison (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Residency is still considered the gold standard for quality medical training, and acquiring a professional identity as a specialist is one of its central elements. Residents obtain this identity through both the educational environment and direct interaction with peers and supervisors. However, modifications in health care and educational routines during the recent coronavirus disease 2019 (COVID-19) pandemic have significantly impaired these channels. This study is part of a qualitative research project to analyze professional identity formation in a medical residency program in obstetrics and gynecology at a public hospital in southern Brazil. The authors conducted 28 semi-structured interviews with medical residents and preceptors, as well as a focus group with the residents, which was recorded, transcribed, and analyzed in an effort to construct major analytical categories. Restricted movement and physical contact have forced the use of alternative means of interpersonal interaction, such as communication through social media or instant messaging applications. This has also affected educational activities, such as morning rounds, lectures, and seminars. These changes represent a significant impact, especially in Brazil, where physical proximity is an important cultural feature, even in the work and school environments. We speculate that this new type of virtual interaction will also affect the formation of professional identity among obstetrician-gynecologists. These findings suggest that medical residency programs should be attentive to changes in resident training to ensure that the specialist profile and the expected skills, which are consolidated over many years, are not lost.
Keywords: medical residency; professional identity; educational environment